Improving Students' Literacy Skills Through the 'Baca Seru' Program at SDN 10 Kamang Baru - Astuti, Mira Wiri; Khotimah , Siti; Muyasyaroh, Alifatul; Syintia, Syintia; Anggraini, Lestari (The Future of Education Journal, 2025)
Literacy skills in elementary school students are a fundamental foundation in the learning process and knowledge development. At SDN 10 Kamang Baru, the literacy ability of students in grades I–III is still relatively low, as indicated by a lack of reading interest and difficulty in understanding reading materials. This study aims to describe the implementation of the Baca Seru (Exciting Reading) Program as an effort to improve students' literacy skills. This research employed a qualitative descriptive approach. The subjects consisted of 40 students from grades I–III and 3 homeroom teachers. Data were collected through observation, interviews, and documentation.The findings show that the Baca Seru Program successfully created an engaging reading atmosphere that motivated students to participate actively in literacy activities. Students demonstrated increased interest in reading, better comprehension skills, and greater confidence in retelling reading content. Activities such as group reading, small group discussions, and reading reflections were effective strategies in enhancing students’ literacy. Teachers played an active role as facilitators who guided and encouraged students throughout the program.Data analysis revealed that 85% of the students showed improved reading comprehension based on daily evaluations and literacy journals. Homeroom teachers also reported a positive change in students’ attitudes and enthusiasm toward reading activities. In conclusion, the Baca Seru Program proved to be effective in improving the literacy skills of grades I–III students at SDN 10 Kamang Baru.